Molecular Chaperones in the Pathogenesis of Amyotrophic Lateral Sclerosis: The Role of HSPB1. Issue 11 (30th August 2016) - Capponi, Simona; Geuens, Thomas; Geroldi, Alessandro; Origone, Paola; Verdiani, Simonetta; Cichero, Elena; Adriaenssens, Elias; De Winter, Vicky; Bandettini di Poggio, Monica; Barberis, Marco; Chiò, Adriano; Fossa, Paola; et al.
Abstract : We report two rare mutations in the small heat shock protein HSPB1 in two unrelated patients with Amyotrophic Lateral Sclerosis (ALS), a severe motor neuron disease. We studied the functional consequences of the mutant HSPB1 protein to explain its effect related to the neurodegeneration. Our study further expands the disease spectrum of mutations in small heat shock proteins. ABSTRACT: Genetic discoveries in amyotrophic lateral sclerosis (ALS) have a significant impact on deciphering molecular mechanisms of motor neuron degeneration but, despite recent advances, the etiology of most sporadic cases remains elusive. Several cellular mechanisms contribute to the motor neuron degeneration in ALS, including RNA metabolism, cellular interactions between neurons and nonneuronal cells, and seeding of misfolded protein with prion‐like propagation. In this scenario, the importance of protein turnover and degradation in motor neuron homeostasis gained increased recognition. In this study, we evaluated the role of the candidate gene HSPB1, a molecular chaperone involved in several proteome‐maintenance functions. In a cohort of 247 unrelated Italian ALS patients, we identified two variants (c.570G>C, p.Gln190His and c.610dupG, p.Ala204Glyfs * 6). Functional characterization of the p.Ala204Glyfs * 6 demonstrated that the mutant protein alters HSPB1 dynamic equilibrium, sequestering the wild‐type protein in a stable dimer and resulting in a loss of chaperone‐like activity. Our results underline the relevance of identifying rare but pathogenic variations in sporadic neurodegenerative diseases, suggesting a possible correlation between specific pathomechanisms linked to HSPB1 mutations and the associated neurological phenotype. Our study provides additional lines of evidence to support the involvement of HSPB1 in the pathogenesis of sporadic ALS.